Henning Steinfeld on the multiple benefits of sustainable livestock - Steinfeld, H. (International Livestock Research Institute, 2017)
Henning Steinfeld, Food and Agriculture Organization of the United Nations discusses multiple benefits from sustainable livestock at the 7th Multi-stakeholder Partnership (MSP) Meeting of the Global Agenda for Sustainable Livestock, Addis Ababa, Ethiopia.